Diagnostic utility of angiogenic biomarkers in pregnant women with suspected preeclampsia: A health economics review - Schlembach, D; Hund, M; Wolf, C; Vatish, M (Elsevier, 2019)
Preeclampsia is a major cause of morbidity and mortality, can be difficult to diagnose, and is associated with significant healthcare costs. The prediction, diagnosis and prognosis of preeclampsia have depended on repeated assessment of women with known risk factors, including intensive monitoring and hospitalization. Many of these women may never go on to develop preeclampsia. Recent developments in the pathogenesis of preeclampsia have shown that maternal serum biomarkers can be used to predict preeclampsia. When the ratio of the anti-angiogenic soluble fms-like tyrosine kinase-1 (sFlt-1) and the pro-angiogenic placental growth factor from the placenta is altered, preeclampsia becomes more likely, providing a diagnostic measurement for risk. The use of angiogenic biomarkers in addition to standard clinical tests can more accurately predict which women are at risk of developing preeclampsia and which are at low or moderate risk, which is likely to streamline the management of pregnant women and target resources in a more efficient way. The studies reviewed here all demonstrate cost savings from use of angiogenic biomarker tests as an addition to standard care.